THE PIVOTAL ROLE OF STOCK EXCHANGES IN FOSTERING A FAVORABLE INVESTMENT CLIMATE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the multifaceted role of stock exchanges as critical institutional mechanisms for improving the investment climate of a nation. A favorable investment climate, characterized by stability, transparency, and efficiency, is a prerequisite for attracting both domestic and foreign capital, which in turn drives economic growth. This paper argues that stock exchanges are not merely platforms for trading securities but are fundamental pillars that enhance the investment climate through several key functions: providing liquidity, facilitating efficient price discovery, enforcing corporate governance standards, and mobilizing domestic savings.The findings suggest that for emerging economies, the development of a well-regulated and efficient stock exchange is a crucial policy lever for reducing capital costs, protecting investors, and ultimately, building a dynamic and sustainable economy. The paper concludes with policy implications for regulators and market operators in developing nations seeking to bolster their own investment climates.